2005
DOI: 10.1007/s10439-005-2504-5
|View full text |Cite
|
Sign up to set email alerts
|

A Model for CD2/CD58-Mediated Adhesion Strengthening

Abstract: Stable cell adhesion is vital for structural integrity and functional efficacy. Yet how low affinity adhesion molecules such as CD2 and CD58 can produce stable cell adhesion is still not completely understood. In this paper, we present a theoretical model that simulates the accumulation of CD2 and CD58 in the contact area of a Jurkat T lymphoblast and a CD58-containing substrate. The cell is assumed to have a spherical shape initially and it is allowed to spread gradually on a circular substrate. Mobile CD2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
6
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
(50 reference statements)
6
6
1
Order By: Relevance
“…A previous analysis of adhesion to bilayers containing the natural CD2 binding partner CD58 found a nonspecific contact area of [29]. We, however, find that the nonspecific contact area is driven to zero in all our fits.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…A previous analysis of adhesion to bilayers containing the natural CD2 binding partner CD58 found a nonspecific contact area of [29]. We, however, find that the nonspecific contact area is driven to zero in all our fits.…”
Section: Discussioncontrasting
confidence: 67%
“…Moreover, in our experiments the small contact regions observed cause only small cellular deformations, and our target Jurkat T cells are substantially easier to deform than some other cell types, such as neutrophils and HL60 cells [28]. However, a recent study of the binding of Jurkat T cells to bilayers containing the natural CD2 ligand CD58 observed that the average contact area did not go to zero as the average number of bridging bonds went to zero [29], and a similar effect may be present in our data. To allow for this possibility, we include a nonspecific adhesion area into our contact area growth law, so that the total contact area is equal to the the nonspecific contribution plus a specific contribution proportional to the total number of bridging bonds:Dividing both sides by , we obtainThe parameter is the bridging bond density required to balance the repulsive force per unit area between the cell and the bilayer.…”
Section: Methodsmentioning
confidence: 51%
“…The 2D Kd measurement has subsequently been refined by modeling CD2 diffusion on cells (Dustin et al, 1997; Zhu et al, 2007; Zhu et al, 2006) and measuring the exclusion of freely diffusing molecules from the contact area (Bromley et al, 2001; Dustin et al, 2007b). The formation of contracts is dependent upon the 2D Kd more than on the kinetics of the interactions, making the 2D Kd an important parameter (Shao et al, 2005). …”
Section: Determination Of Two-dimensional Affinitymentioning
confidence: 99%
“…Since then, a good variety of mechanics models have been introduced, where the effects of fluid dynamics (Liu et al, 2006), fluid-structure interaction (Park et al, 2007), substrate pattern (Das and Du, 2008;Deshpande et al, 2008), thermodynamic considerations (Deshpande et al, 2008;Sarvestani, 2010) and other attributes (Nicolas et al, 2004;Ni and Chiang, 2007;Liu et al, 2007;Xu et al, 2009;Shao et al, 2005) were addressed. The kinetic model based on the study of the adhesion of a single giant vesicle onto a solid surface showed that the adhesion dynamics can be understood as a process of nucleation and growth (Boulbitch et al, 2001).…”
Section: Introductionmentioning
confidence: 99%